2018
DOI: 10.1021/acs.jmedchem.8b00315
|View full text |Cite
|
Sign up to set email alerts
|

Novel Allosteric Activators for Ferroptosis Regulator Glutathione Peroxidase 4

Abstract: Glutathione peroxidase 4 (GPX4) is essential for cell membrane repair, inflammation suppression, and ferroptosis inhibition. GPX4 upregulation provides unique drug discovery opportunities for inflammation and ferroptosis-related diseases. However, rational design of protein activators is challenging. Until now, no compound has been reported to activate the enzyme activity of GPX4. Here, we identified a potential allosteric site in GPX4 and successfully found eight GPX4 activators using a novel computational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 37 publications
2
86
0
Order By: Relevance
“…In the previous study, we have identified a potential allosteric site in the crystal structure of human GPX4 U46C mutant (hGPX4-C, PDB entry 2OBI; Scheerer et al, 2007 ) using the binding site detection program CAVITY ( Yuan et al, 2011 , 2013 ) and the allosteric site motion correlation analysis program CorrSite ( Ma et al, 2016 ). We found a series of substituted 4-thioureidobenzenesulfonamide compounds that can activate GPX4 enzyme activity and suppress ferroptosis ( Li et al, 2018 ). In the present study, we used a similar virtual screen procedure and the predicted allosteric site ( Figure 2A ) to screen for compounds with anti-inflammatory activity and novel chemical scaffold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, we have identified a potential allosteric site in the crystal structure of human GPX4 U46C mutant (hGPX4-C, PDB entry 2OBI; Scheerer et al, 2007 ) using the binding site detection program CAVITY ( Yuan et al, 2011 , 2013 ) and the allosteric site motion correlation analysis program CorrSite ( Ma et al, 2016 ). We found a series of substituted 4-thioureidobenzenesulfonamide compounds that can activate GPX4 enzyme activity and suppress ferroptosis ( Li et al, 2018 ). In the present study, we used a similar virtual screen procedure and the predicted allosteric site ( Figure 2A ) to screen for compounds with anti-inflammatory activity and novel chemical scaffold.…”
Section: Resultsmentioning
confidence: 99%
“…The details of allosteric site prediction and virtual screen are described in a recent report ( Li et al, 2018 ). Potential allosteric site in GPX4 was identified using the CAVITY ( Yuan et al, 2011 , 2013 ) and CorrSite ( Ma et al, 2016 ) program, and then applied to screen for potential allosteric activator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the present study, ferroptosis in human glioma cells was assessed by measuring the levels of GPX4, 5-, 12-and 15-HETE. GPX4 is an important membrane lipid peroxidase reductase, and the downregulation of GPX4 causes the accumulation of reactive oxygen species (ROS) on membrane lipids, which leads to ferroptosis (36). The latter three are lipid peroxidation products that are associated with the deposition of ferritin in ferroptosis, and recognized as indicators of ferroptosis levels (20,26).…”
Section: Ferroptosis Levels Are Reduced In Human Glioma Cellsmentioning
confidence: 99%
“…Understanding allosteric signaling and predicting allosteric binding sites are at the cutting edge of drug discovery [40][41][42][43][44][45] . The Allosteric Database [46][47][48] Action at a distance is a key feature of the allosteric effect; the effector binds a site topographically distinct from the orthosteric site.…”
Section: Allosteric Signalingmentioning
confidence: 99%